(untitled) (Proceedings of the International Conference on Education, 2021)
The purpose of this study was to gather recommendations from organizational leaders, faculty, and students as an input to curricular reform for healthcare programs. The method was a qualitative research with a focus group and interviews with 26 leaders, faculty, and students. Focus group participants were leaders who dialogued reflect on the future tasks of healthcare professionals of the future. The data from the focus group was analysed learning environment dimensions. Five themes emerged from the focus groups. Eight leaders from associations, hospitals and medical schools remarked the importance on: 1) patient centered care, emphasis on prevention and well-being, 2) professionalism and identity formation, 4) innovation, research, and technology, 5) leadership for healthcare systems. Interviews showed that biomedical contents develop critical thinking and self-directed learning. Interviewees recommended starting patient care earlier on the program. There was a significant curricular reform to address opportunities and suggestions from participants. Perspectives from different stakeholders helped to develop inter-professional education for five programs. Patient Centeredness is learned from the first year of the programs through challenge-based learning. This approach which started on August 2019 is intended to develop leaders for the improvement of the healthcare systems. Even that scientific and technological advances demand radical change for universities, there are centuries of history that restrain them. At Tecnologico de Monterrey, School of Medicine and Health Sciences an integrated curriculum with challenges for wellness instead of diseases is now a reality.